2015
DOI: 10.1002/iid3.55
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel CD8+ T cell epitopes in human herpesvirus 6B U11 and U90

Abstract: Human herpesvirus 6B (HHV6B) infects over 90% of the population, and normally establishes a latent infection, where episodes of reactivation are asymptomatic. However, in immunocompromised patients HHV6B reactivation is associated with high morbidity and mortality. Cellular immunotherapy has been utilised against other herpesvirus in immunocompromised settings. However, limited information on the immune response against HHV6B has hampered the development of immunotherapy for HHV6B-driven disease. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…As previously observed [56], we found that infection of SupT1.CIITA cells with HHV-6B resulted in downregulation of MHC-class I. It is possible that when the cytotoxic CD8 T cells have been compromised by any of the immunomodulatory mechanisms used by the virus to interfere with MHC-I presentation and CD8 response [10,13,18,19,21], CD4 T cells may become more prominent in the control of the virus. A more detailed phenotypic and functional characterization of CD4 T cell responding to HHV-6B in healthy donors could shed light on the specific responding subset, as well as its effector and functional capacities.…”
supporting
confidence: 79%
“…As previously observed [56], we found that infection of SupT1.CIITA cells with HHV-6B resulted in downregulation of MHC-class I. It is possible that when the cytotoxic CD8 T cells have been compromised by any of the immunomodulatory mechanisms used by the virus to interfere with MHC-I presentation and CD8 response [10,13,18,19,21], CD4 T cells may become more prominent in the control of the virus. A more detailed phenotypic and functional characterization of CD4 T cell responding to HHV-6B in healthy donors could shed light on the specific responding subset, as well as its effector and functional capacities.…”
supporting
confidence: 79%
“…The novel prevalent antigen U95, recognized by 44% of participants and confirmed by peptides, has no known HCMV homolog but is a highly expressed immediate early gene (46). Therefore, it may also be a rational target for cell-based immunotherapies alongside the immediate early U90 protein, a previously described antigen (31,32,34). Peptide epitopes confirmed here for U14, U90, and U95 had sequence homology to the related betaherpesviruses HHV-6A (all epitopes) and HHV-7 (nine epitopes) (see Table S2 in the supplemental material), suggesting possible cross-reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Because HHV-6 and CMV are genetically related betaherpesviruses, some studies have focused on the HHV-6 homologs of known CMV antigenic proteins. These studies have identified HHV-6 U11, U14, U54, and U90, the homologs of CMV UL32, UL25, UL82/83, and IE1, respectively, as targets for CD4 or CD8 T cells (31)(32)(33)(34). Other studies have taken a cross-sectional approach by testing libraries of peptides that were predicted to bind to a particular HLA allele: DRB1*0101 for CD4 T cells (30,35) or HLA-B*0801 for CD8 T cells (36).…”
mentioning
confidence: 99%
“…However, in contrast to those of other human herpesviruses, HHV-6-specific T cells have been difficult to characterize so far. Indeed, HHV-6-specific T-cell responses were reported to be absent or of really low frequency in peripheral blood (20,21,23,32,33), particularly in regard to CD8 ϩ T cells (34). It has also been reported that HHV-6A impacts T cell subsets differentially; i.e., in response to HHV-6A stimulation, naive or central memory cells were more prone to apoptosis, whereas proliferation was increased for the late memory compartment (35).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in contrast to that for HCMV, knowledge of HHV-6-specific T-cell responses is limited. This caveat may result from the difficulty of detecting HHV-6-specific T cells ex vivo in healthy adults (19)(20)(21). Indeed, most studies have performed analyses after in vitro expansion (22,23).…”
mentioning
confidence: 99%